CITRA PEREMPUAN TOKOH NISA DALAM NOVEL IPAR ADALAH MAUT KARYA ELIZASIFAA (KAJIAN ANALISIS ISI) - Novia Novia; Afif Rofii; Uli Wahyuni (Universitas Batanghari, 2026)
The research entitled The Image of the Female Character Nisa in the Novel Ipar Adalah Maut by Elizasifaa (Content Analysis Study) is motivated by a social phenomenon that illustrates that the image of women has recently begun to shift towards the negative. Today's women sometimes go beyond the limits of life's nature to the point of distorting their image. Therefore, this study aims to describe the form of the female image in the novel Ipar Adalah Maut. This study uses a qualitative descriptive research type. The descriptive method is used to describe the image of the female character Nisa in terms of its form. While the qualitative approach is used to analyze the form of the female image of Nisa in this novel. The data collection technique is carried out by repeatedly reading and marking the form of the female image of Nisa in this novel. The collected data are then analyzed based on the theory used as a reference. The results of this study found 52 quotations related to the image of the female character Nisa in Ipar Adalah Maut by Elizasifaa. Quotes on the image of the female aspect of steadfastness were found in 14 quotations. The aspect of devotion to parents was found in 29 quotations. The aspect of not giving up easily was found in 9 quotations. Thus, the most dominant aspect of Nisa's female image is her devotion to her parents. This illustrates Nisa's high level of devotion to her parents.